Analisis Ketepatan Istilah Terminologi Medis Penyakit Sistem Respirasi Sesuai Klasifikasi Penyakit ICD-10 di Puskesmas Kecamatan Grogol Petamburan - Febri Irawan; Deasy Rosmala Dewi; Nanda Rumana; Muniroh (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Medical terminology is medical language which is a liaison between health workers' facilities. Medical terminology written on the diagnosis should be written by the right health care worker so that it has informative value in order to assist the coding officer in selecting the lead term for determining the diagnosis code. The purpose of this study was to analyze the accuracy of medical terminology in respiratory system diseases according to the ICD-10 disease classification at the Grogol Petamburan District Health Center. Using a quantitative descriptive research method on 90 samples of medical record cases of the respiratory system in August 2020. The sampling technique used was random sampling. The size was determined randomly using the slovin formula. The results showed that the accuracy of using medical terminology in medical records was 74 (82%) and inaccuracy in the use of medical terminology 16 (18%) using abbreviations, Indonesian language, and letter/spelling errors. Factors causing the inaccuracy. The Puskesmas already has a SOP for recording medical records, but the service points have not been explained in detail according to the SOAP, especially the assessment which requires doctors to write diagnoses using medical terminology according to the ICD-10 disease classification. Then the large number of patients can be a factor causing the doctor's inaccuracy in writing a diagnosis. It is recommended to the head of the medical record to evaluate the accuracy of outpatient medical terminology according to the ICD-10 disease classification, so that there are no inaccuracies in medical terminology using Indonesian language, abbreviations, and spelling errors.